2004
DOI: 10.1128/jvi.78.10.5299-5310.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mutated Form of the Newcastle Disease Virus Hemagglutinin-Neuraminidase Interacts with the Homologous Fusion Protein despite Deficiencies in both Receptor Recognition and Fusion Promotion

Abstract: The Newcastle disease virus (NDV) hemagglutinin-neuraminidase (HN) protein mediates attachment to cellular receptors. The fusion (F) protein promotes viral entry and spread. However, fusion is dependent on a virus-specific interaction between the two proteins that can be detected at the cell surface by a coimmunoprecipitation assay. A point mutation of I175E in the neuraminidase (NA) active site converts the HN of the Australia-Victoria isolate of the virus to a form that can interact with the F protein despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
66
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 32 publications
7
66
1
Order By: Relevance
“…The globular head consists of a six-bladed ␤-sheet propeller with a centrally located sialic acid binding site (site I) that also mediates neuraminidase (NA) activity (4). Many mutations in this site, including K236R, abolish receptor binding, NA, and fusion (7), as well as the ability of HN to interact with F at the cell surface (14). These findings, along with the results of bimolecular complementation studies (2), are consistent with HN and F promoting fusion by the provocateur (2) mechanism, which asserts that the HN-F interaction is triggered at the surface by receptor binding.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The globular head consists of a six-bladed ␤-sheet propeller with a centrally located sialic acid binding site (site I) that also mediates neuraminidase (NA) activity (4). Many mutations in this site, including K236R, abolish receptor binding, NA, and fusion (7), as well as the ability of HN to interact with F at the cell surface (14). These findings, along with the results of bimolecular complementation studies (2), are consistent with HN and F promoting fusion by the provocateur (2) mechanism, which asserts that the HN-F interaction is triggered at the surface by receptor binding.…”
supporting
confidence: 76%
“…1C). As a negative control, HN carrying a K236R mutation in site I fails to co-IP with F, as previously demonstrated (14). We have previously identified mutations for residues A89, L90, and L94 in the stalk of NDV HN, which modulate proportionately fusion and HN-F complex formation, consistent with this domain mediating the interaction with F (15).…”
mentioning
confidence: 66%
“…The abilities of wt and mutated HN proteins to interact with cleavage site-mutated (csm) F at the surfaces of transfected BHK cells were assayed at 16 h posttransfection using a previously described co-IP assay (26).…”
Section: Methodsmentioning
confidence: 99%
“…The ability of HN to interact with F and L289A-F at the surface of transfected BHK cells was assayed at 16 h posttransfection, using a co-IP assay described previously (21). Briefly, monolayers consisting of equal numbers of cells were starved and labeled, prior to biotinylation of cell surface proteins.…”
Section: Recombinant Expression Vectorsmentioning
confidence: 99%
“…This contribution is virus specific, in that most heterologous combinations of HN and F do not result in fusion (20). The role that HN plays in Fmediated fusion involves an interaction between the two proteins at the cell surface (7,21,33). Through the construction and evaluation of chimeric HN proteins composed of domains from proteins derived from heterologous viruses, it has been shown that the stalk region of the HN spike determines its specificity for the homologous F protein (8,29,31,32).…”
mentioning
confidence: 99%